High-flow nasal cannula for stabilisation of very premature infants: A prospective observational study - Jonáš, Klára; Lamberská, Tereza; Nguyen, Truong An; Kudrna, Petr; Plavka, Richard (Acta paediatrica (Oslo, Norway, 2025)
AIM: To assess the feasibility, safety and efficacy of using a high-flow nasal cannula (HFNC) for stabilising very preterm infants after birth. METHODS: A prospective observational study included preterm infants born at 28 + 0 to 31 + 6 weeks' gestation between February 2021 and December 2022 at the General University Hospital in Prague. Following delayed cord clamping, HFNC was administered at a flow rate of 8 L/min through the infants' nostrils. Criteria for switching to continuous positive airway pressure (CPAP) or positive pressure ventilation (PPV) included persistent bradycardia in the first few minutes or low saturation of oxygen (SpO2) after 5 min, respectively. RESULTS: Of the 65 infants enrolled in the study, 56 (86%) were successfully stabilised exclusively using HFNC while 7 (11%) required PPV. Additionally, 52 (80%) infants achieved SpO2 > 80% at 5 min, and 54 (83%) infants were successfully treated with HFNC within the first 3 h of life. CONCLUSION: The primary use of HFNC seems to be an appropriate alternative to CPAP for the stabilisation of very premature infants after birth and subsequent transfer to the NICU. A randomised trial comparing HFNC and CPAP in the delivery room will enable to answer the questions raised in this study.
Keywords: Cannula; lidé; oxygenoterapie; prospektivní studie; Female; delivery room; very premature infant; Infant, Premature; Humans; Infant, Newborn; novorozenci extrémně nezralí; Oxygen Inhalation Therapy; Prospective Studies; Continuous Positive Airway Pressure; Feasibility Studies; mužské pohlaví; novorozenec nedonošený; novorozenec; kanyla; positive pressure ventilation; ženské pohlaví; high‐flow nasal cannula; Male; continuous positive airway pressure; trvalý přetlak v dýchacích cestách; studie proveditelnosti; Infant, Extremely Premature